2022
DOI: 10.3389/fvets.2022.806069
|View full text |Cite
|
Sign up to set email alerts
|

Pre-conditioning Strategies for Mesenchymal Stromal/Stem Cells in Inflammatory Conditions of Livestock Species

Abstract: Mesenchymal stem/stromal cells (MSCs) therapy has been a cornerstone of regenerative medicine in humans and animals since their identification in 1968. MSCs can interact and modulate the activity of practically all cellular components of the immune response, either through cell-cell contact or paracrine secretion of soluble mediators, which makes them an attractive alternative to conventional therapies for the treatment of chronic inflammatory and immune-mediated diseases. Many of the mechanisms described as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…The complex microenvironment that internal and external MSCs faced and encountered in fibrosis diseases could bring opposite outcomes for their functions. Based on this information, pre-conditioning strategies for MSCs have been encouraged to be used in preclinical and clinical trials, including physical and chemical pre-conditioning strategies such as hypoxic conditions, with inflammatory cytokines, or with different pattern recognition receptor ligands [ 268 , 269 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex microenvironment that internal and external MSCs faced and encountered in fibrosis diseases could bring opposite outcomes for their functions. Based on this information, pre-conditioning strategies for MSCs have been encouraged to be used in preclinical and clinical trials, including physical and chemical pre-conditioning strategies such as hypoxic conditions, with inflammatory cytokines, or with different pattern recognition receptor ligands [ 268 , 269 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the stem cell source, differences in secretome composition are significant when comparing fetal or adult donors [ 75 , 76 ]. Furthermore, pre-conditioning of the donor cells either with various compounds or by modification of the culture conditions leads to altered secretome profiles [ 77 , 78 , 79 , 80 ]. Another big obstacle when comparing CM and its subfraction is the standardization strategy for studies, the optimal dosage of the treatment, and the number of doses.…”
Section: Discussionmentioning
confidence: 99%
“…This potential use of MSC in cattle was recently discussed [7]. Some in-vitro and in-vivo studies demonstrated encouraging immunomodulating, antiinflammatory and antimicrobial effects in mammary and uterus cell systems and animal models [5,[8][9][10][11][12][13]. However, the feasibility and efficacy of MSC-based therapy for mastitis and metritis are still unknown and further research is required.…”
Section: Introductionmentioning
confidence: 99%